Protein phosphatase 2A regulates xanthine oxidase-derived ROS production in macrophages and influx of inflammatory monocytes in a murine gout model - Elsayed, Sandy; Elsaid, Khaled A. (Frontiers in Pharmacology, 2022)
Background Gout is a common arthritis, due to deposition of monosodium urate (MSU) crystals which results in IL-1 secretion by tissue-resident macrophages. Xanthine oxidase (XO) catalyzes uric acid (UA) production and in the process, reactive oxygen species (ROS) are generated which contributes to NLRP3 inflammasome activation. Protein phosphatase 2A (PP2A) may be involved in regulating inflammatory pathways in macrophages. The objective of this study was to investigate whether PP2A regulates gout inflammation, mediated by XO activity modulation. We studied UA and ROS generations in MSU stimulated murine bone marrow derived macrophages (BMDMs) in response to fingolimod phosphate, a PP2A activator, and compared its anti-inflammatory efficacy to that of an XO inhibitor, febuxostat. Methods BMDMs were stimulated with MSU, GM-CSF/IL-1or nigericin  fingolimod (2.5M) or febuxostat (200M) and UA levels, ROS, XO, and PP2A activities, Xdh (XO) expression and secreted IL-1 levels were determined. PP2A activity and IL-1 in MSU stimulated BMDMs  N-acetylcysteine (NAC) (10M)  okadaic acid (a PP2A inhibitor) were also determined. M1 polarization of BMDMs in response to MSU  fingolimod treatment was assessed by a combination of iNOS expression and multiplex cytokine assay. The in vivo efficacy of fingolimod was assessed in a murine peritoneal model of acute gout where peritoneal lavages were studied for pro-inflammatory classical monocytes (CMs), anti-inflammatory nonclassical monocytes (NCMs) and neutrophils by flow cytometry and IL-1 by ELISA. Results Fingolimod reduced intracellular and secreted UA levels (p<0.05), Xdh expression (p<0.001), XO activity (p<0.001), ROS generation (p<0.0001) and IL-1 secretion (p<0.0001), whereas febuxostat enhanced PP2A activity (p<0.05). NAC treatment enhanced PP2A activity and reduced XO activity and PP2A restoration mediated NAC’s efficacy as co-treatment with okadaic acid increased IL-1 secretion (p<0.05). Nigericin activated caspase-1 and reduced PP2A activity (p<0.001) and fingolimod reduced caspase-1 activity in BMDMs (p<0.001). Fingolimod reduced iNOS expression (p<0.0001) and secretion of IL-6 and TNF- (p<0.05). Fingolimod reduced CMs (p<0.0001), neutrophil (p<0.001) and IL-1 (p<0.05) lavage levels while increasing NCMs (p<0.001). Conclusions Macrophage PP2A is inactivated in acute gout by ROS and a PP2A activator exhibited a broad anti-inflammatory effect in acute gout in vitro and in vivo.